BeYOND: Biomarkers in younger‐onset neurocognitive disorders — The first 50 participants: Neuropsychiatry and behavioral neurology/Neuropsychiatry. (7th December 2020) - Loi, Samantha M.; Eratne, Dhamidhu; Waterfang, Mark; Kelso, Wendy; Farrand, Sarah; Goh, Anita M.Y.; Chadunow, Carolyn; Ravenfar, Parsa Seyed; Watson, Rosie; Evans, Andrew H.; Vidaurre, Lesley; Velakoulis, Dennis
Abstract: Background: There are currently 28000 people in Australia with younger‐onset dementia (YOD). A recent review of younger‐onset dementia cohorts (Loi SM et al. submitted) suggested that there needs to be more detailed study in this heterogenous group in order to glean more clinically relevant information. For example, our group (Eratne D et al. 2020) investigated the utility of cerebrospinal fluid (CSF) neurofilament light (NfL) chain in a group of people with a range of psychiatric and neurodegenerative disorders and reported that NfL could distinguish between these two broad disorders, demonstrating the benefits in studying a large range of YODs. BeYOND (Biomarkers in younger‐onset neurocognitive disorders) was established as a longitudinal cohort of younger people presenting with neurocognitive symptoms to a clinical diagnostic service, with the aim of identifying clinical and investigational biomarkers which can inform diagnostic and psychosocial outcomes in a clinically heterogenous population. Method: Patients are prospectively recruited during their index presentation to Neuropsychiatry, Royal Melbourne Hospital, Australia. Neuropsychiatry is a tertiary specialist service which provides diagnostic work‐up for patients with cognitive, psychiatric and neurological symptoms. The diagnostic process includes baseline and 18 month assessments of clinical and diagnostic outcomes including CSF and blood biomarkers, cognition, neuroimaging and psychosocial (including caregiver). Results: To date, 50 participants have been recruited (17 females, mean age 55). Thirty of had a dementia diagnosis (including Alzheimer's dementia, frontotemporal dementia and Huntington's disease), with the remainder having a psychiatric disorder (including depression and schizophrenia) as principle diagnosis. All participants have had clinical, neuropsychology and imaging. Eleven have had a lumbar puncture. Twenty participants have had a research blood panel for genetic analysis)and 12 had quantitative susceptibility mapping imaging. Conclusion: The diagnosis of neurodegenerative disorders in younger people can be difficult and is often associated with diagnostic delays (Draper B et al. 2016). The BeYOND study aims to longitudinally assess younger patients with suspected neurodegenerative disease in order to improve diagnostic and psychosocial outcomes for this population. References: Loi SM et al. J Neuropsychiatry Clin Neuroscience. Submitted 23/1/2020. Eratne D et al. ANZJP . 54 (1): 57‐67. 2020. Draper B et al. Int J Geriatr Psychiatry. 31 (11): 1217‐1224. 2016.